Endotoxin-Induced Emphysema Exacerbation: A Novel Model of Chronic Obstructive Pulmonary Disease Exacerbations Causing Cardiopulmonary Impairment and Diaphragm Dysfunction - de Oliveira, Milena Vasconcellos; Rocha, Nazareth de Novaes; Santos, Raquel Souza; Rocco, Marcella Rieken Macedo; de Magalhães, Raquel Ferreira; Silva, Johnatas Dutra; Souza, Sergio Augusto Lopes; Capelozzi, Vera Luiza; Pelosi, Paolo; Silva, Pedro Leme; Rocco, Patricia Rieken Macedo (Frontiers in Physiology, 2019)
Chronic obstructive pulmonary disease (COPD) is a progressive disorder of the lung parenchyma which also involves extrapulmonary manifestations, such as cardiovascular impairment, diaphragm dysfunction, and frequent exacerbations. The development of animal models is important to elucidate the pathophysiology of COPD exacerbations and enable analysis of possible therapeutic approaches. We aimed to characterize a model of acute emphysema exacerbation and evaluate its consequences on the lung, heart, and diaphragm. Twenty-four Wistar rats were randomly assigned into one of two groups: control (C) or emphysema (ELA). In ELA group, animals received four intratracheal instillations of pancreatic porcine elastase (PPE) at 1-week intervals. The C group received saline under the same protocol. Five weeks after the last instillation, C and ELA animals received saline (SAL) or E. coli lipopolysaccharide (LPS) (200 microg in 200 microl) intratracheally. Twenty-four hours after saline or endotoxin administration, arterial blood gases, lung inflammation and morphometry, collagen fiber content, and lung mechanics were analyzed. Echocardiography, diaphragm ultrasonography (US), and computed tomography (CT) of the chest were done. ELA-LPS animals, compared to ELA-SAL, exhibited decreased arterial oxygenation; increases in alveolar collapse (p<0.0001), relative neutrophil counts (p=0.007), levels of cytokine-induced neutrophil chemoattractant-1, interleukin (IL)-1beta, tumor necrosis factor-alpha, IL-6, and vascular endothelial growth factor in lung tissue, collagen fiber deposition in alveolar septa, airways, and pulmonary vessel walls, and dynamic lung elastance (p<0.0001); reduced pulmonary acceleration time/ejection time ratio, (an indirect index of pulmonary arterial hypertension); decreased diaphragm thickening fraction and excursion; and areas of emphysema associated with heterogeneous alveolar opacities on chest CT. In conclusion, we developed a model of endotoxin-induced emphysema exacerbation that affected not only the lungs but also the heart and diaphragm, thus resembling several features of human disease. This model of emphysema should allow preclinical testing of novel therapies with potential for translation into clinical practice.